Communication strategies used by women to influence male partners to seek professional help for mental health problems: A qualitative study. (30th April 2019) - Rooney, Lauren; John, Mary; Morison, Linda
Abstract: Objective: Previous research suggests that female partners have a key role in encouraging men to seek help from a mental health professional. This study investigated the communication forms that female partners use to encourage their male partners to seek help for a mental health problem. Methods: Fifteen women with experience of working with a partner to seek help, aged 28–71 years, participated in a semi‐structured interview. The interviews were analysed using Thematic Analysis. Results: The main themes indicated that the women initially undertook "Role Adaption/s" and changed their roles to reduce the stress on their male partners. They made "attempts to activate engagement" with their wellbeing through conversations about mental health and the benefits of help‐seeking. Discussions began with "gentle" communications, such as hinting and sowing seeds, and escalated to more assertive communications which could be conceived of as "threats" and "emotional blackmail, " if the women were concerned their partners were not seeking help or were at risk of suicide. Finally, the couples entered "Attempted Resolution" where they had conversations around help‐seeking, and/or their male partner considered suicide. Conclusions: Female partners perceived themselves as having a key role in supporting men to seek help from a professional and in maintaining their partner's safety and they adapted their communication strategies to implement this. Access to high‐quality information and some amendments to general practitioner confidentiality would facilitate them in their role.